Preoperative application of carbon nanoparticles in transoral endoscopic thyroidectomy vestibular approach for papillary thyroid cancer - Wang, Yonghui; Zhang, Li; Huang, Jinning; Wang, Liquan (Frontiers in Oncology, 2023)
Background Carbon nanoparticles (CNs) have been widely used in the protection of the parathyroid gland and act as a tracer agent in central lymph node dissection. However, the right time for CN injection has not been well illustrated in the transoral endoscopic thyroidectomy vestibular approach (TOETVA). The purpose of this study was to evaluate the safety and feasibility of the preoperative injection of CNs in TOETVA for papillary thyroid cancer. Methods From October 2021 to October 2022, a total of 53 consecutive patients with PTC were retrospectively analyzed. All patients underwent unilateral thyroidectomy via the TOETVA. The patients were divided into the preoperative group (n = 28) and the intraoperative group (n = 25) according to CN injection time. In the preoperative group, 0.2 ml of CNs were injected into the thyroid lobules with malignant nodules 1 h before surgery. The numbers of total central lymph node (CLN) and metastatic central lymph node (CLNM), parathyroid autotransplantation, accidental removal of the parathyroid, and the parathyroid hormone level were recorded and analyzed. Results The leakage of CNs happened more frequently in the intraoperative group than in the preoperative group (P = 0.002). The mean number of retrieved CLN and CLNM was similar in the preoperative group and the intraoperative group. In parathyroid protection, more parathyroid was discovered in the preoperative group than in the intraoperative group (1.57 ± 0.54 vs. 1.47 ± 0.50, P = 0.002), but less parathyroid autotransplantation (P = 0.004) and accidental removal of the parathyroid (P = 0.036) were discovered in the preoperative group. However, the PTH level between the two groups was similar after the first day and the first month. Conclusion The preoperative injection of CNs is a safe and effective method to protect the parathyroid glands (PGs) in patients with PTC undergoing TOETVA. However, the value of preoperative injection of CNs in TOETVA for central lymph node dissection needs to be further studied.